Process Chain for the Fabrication of a Custom 3D Barrier for Guided Bone Regeneration - Ramírez Cedillo, Erick; Lara Padilla, Hernán; Zamudio Peña, Luis F.; Rodríguez García, Aída; Ruiz Huerta, Leopoldo; Ruiz, Alberto Caballero; Siller, Héctor R. (2017)
Guided Bone Regeneration (GBR) is a surgical procedure that consists in the use of barrier membranes to cover bone defects caused by trauma, periodontal disease and other pathologies. These barriers allow the proliferation of bone cells, and prevent the invasion of the defect by non-osteogenic cells (connective and epithelium) in patients with a lack of horizontal and/or vertical bone. This process is essential for the successful dental implant placement. Additive manufacturing (AM) is emerging as an important tool for biomedical applications, especially for regenerative medicine and tissue engineering. This paper proposes a process chain for the fabrication of a custom barrier from cone beam computed tomography (CBCT) as Digital Imaging and Communication in Medicine (DICOM) files obtained from a patient with vertical bone resorption of the anterior maxilla. DICOM files have been processed with Invesalius 3.0 to obtain the tridimensional (3D) anatomy of the region of interest. This 3D model was cleaned, fixed, and smoothed. The prototyped model of the patient’s bone defect was further processed in Rhinoceros to offer a 3D architecture for cell growth. To obtain information of the thermal and mechanical properties a finite element method (FEM) was assessed. The prototype obtained was produced with fused deposition modeling (FDM) an additive manufacturing technology